An optimized and automated approach to quantifying channelrhodopsin photocurrent kinetics - Prignano, Lindsey; Faal, Siamak G.; Hera, Adriana; Dempski, Robert E. (Analytical biochemistry, 2019)
Channelrhodopsins are light-activated ion channels that enable targetable activation or inhibition of excitable cells with light. Ion conductance can generally be described by a four step photocycle, which includes two open and two closed states. While a complete understanding of channelrhodopsin function cannot be understood in the absence of kinetic modeling, model fitting requires manual fitting, which is laborious and technically complicated for non-experts. To enhance analysis of photocurrent data, this manuscript describes a fitting program where electrophysiology data can be automatically and quantitatively analyzed. Significant improvement in this program when compared to our previous version includes 1) the ability to automatically find the experiment start time using the derivative of the current signal, 2) utilizing the Object Oriented Programing (OPP) paradigm which is significantly more reliable if the code is used by people with little to no programming experience and 3) the distribution of the code is simplified to sharing a single MATLAB file, including rigorous comments throughout. To demonstrate the utility of this program, we show automated fitting of photocurrents from two member proteins: channelrhodopsin-2 and a chimera between channelrhodopsin-1 and channelrhodopsin-2 (C1C2). •Channelrhodopsins have revolutionized neuroscience studies.•Channelrhodopsin has enabled spatial and temporal control over excitable cells.•Quantitative analysis of channelrhodopsin ion conductance is complicated.•We describe an automated program to provide quanitative channel conductance data.